The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7759/cureus.8728
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties of Small-Size Hamstring Autografts

Abstract: To evaluate small-size hamstring (HS) autografts for biomechanical properties and determine a threshold diameter necessary for appropriate reconstruction. Methods In a controlled laboratory setting, biomechanical testing was performed upon 15 hamstring autografts. The grafts were divided into three groups by diameter, with five grafts each at diameter sizes of 6, 7, and 8 mm. Testing of the specimens was performed using an MTS 858 (Materials Testing System, Eden Prairie, MN). We determined load to failure by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The samples were tested using a load frame (Instron 5944, Instron, Canton, MA, USA) (Fig. 1 ), first preloaded to 10 N to remove any slack in the system and cycled ten times from 50 to 250 N at a rate of 1 mm/s to remove any viscoelastic effects during testing [ 18 , 19 ]. The grafts were loaded to failure at 100 N/s.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were tested using a load frame (Instron 5944, Instron, Canton, MA, USA) (Fig. 1 ), first preloaded to 10 N to remove any slack in the system and cycled ten times from 50 to 250 N at a rate of 1 mm/s to remove any viscoelastic effects during testing [ 18 , 19 ]. The grafts were loaded to failure at 100 N/s.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, surgical experience and magnetic resonance imaging (MRI) studies show significant discrepancies in hamstring size among the population [ 10 , 11 ]. Some biomechanical studies suggest that larger graft sizes are more beneficial as they account for potential strength reduction during graft healing [ 12 ]. Previous studies have also shown that smaller graft sizes are correlated with an increased risk of failure in these patients [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some biomechanical studies suggest that larger graft sizes are more beneficial as they account for potential strength reduction during graft healing [ 12 ]. Previous studies have also shown that smaller graft sizes are correlated with an increased risk of failure in these patients [ 12 , 13 ]. Other studies have also shown that younger age may be associated with graft failure.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Advantages to the use of hamstring (HS) autograft in comparison with other autograft choices include decreased levels postoperative knee pain, absence of violation to the extensor mechanism, and greater graft tensile strength. 2 , 3 , 4 , 5 However, one notable limitation to the use of HS autografts for ACLR is unpredictable graft sizes, which can range from 6 to 9 mm. 4 , 6 , 7 Although certain patient-specific demographics and cross-sectional measurements on magnetic resonance imaging may be used to help predict legs that will yield a HS autograft diameter less than 8 mm, grafts not exceeding this threshold have been demonstrated to be associated with an increased risk of failure of ACLR.…”
mentioning
confidence: 99%